Factors Leading to Prolonged Hospital Stay in Patients Undegoing Laproscopic Cholecystectomy at Tertiary Care Hospital, Karachi - Unaiza Erum, Murk Lakhani, Erum Kazim, Bushra Kiran Naeem, Mirza Arsalan Baig, Hassan Shahab (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of prolonged hospital stay and its associated factors in patients undergoing laparoscopic cholecystectomy for symptomatic cholelithiasis at Tertiary Care Hospital, Karachi. Methods: After the ethical approval from College of Physicians and Surgeons Pakistan, this descriptive study, was conducted at Department of Surgery, Civil Hospital, Karachi, from 08-06-2021 till 08-01-22. Data was prospectively collected from patients after taking a verbal consent. 88 patients who met the diagnostic criteria were included. Quantitative data was presented as simple descriptive statistics giving mean and standard deviation and qualitative variables was presented as frequency and percentages. Effect modifiers were controlled through stratification to see the effect of these on the outcome variable. Post stratification chi square test was applied taking p-value of ≤0.05 as significant Results: A total of 88 patients who met the inclusion and exclusion criteria were included in this study. Mean age, duration of surgery, BMI, height and weight in our study was 50.14±10.49 years, 75.25±20.87 minutes, 29.66±2.56 kg/m2, and 152.3±10.28 cm and 76.9±8.87 kg. Out of 88 patients, 26 (29.5%) and 62 (70.5%) had and did not have prolonged hospital stay. Conclusion: It is possible to shorten the length of time spent in the hospital after surgery if the patient is carefully evaluated beforehand, the operation is performed with precision, and the patient is well cared for afterward. Keywords: Prolonged hospital stay, laparoscopic cholecystectomy, symptomatic cholelithiasis and factors.